2017
DOI: 10.1002/hbm.23675
|View full text |Cite
|
Sign up to set email alerts
|

Specifying the brain anatomy underlying temporo-parietal junction activations for theory of mind: A review using probabilistic atlases from different imaging modalities

Abstract: In this quantitative review, we specified the anatomical basis of brain activity reported in the Temporo-Parietal Junction (TPJ) in Theory of Mind (ToM) research. Using probabilistic brain atlases, we labeled TPJ peak coordinates reported in the literature. This was carried out for four different atlas modalities: (i) gyral-parcellation, (ii) sulco-gyral parcellation, (iii) cytoarchitectonic parcellation and (iv) connectivity-based parcellation. In addition, our review distinguished between two ToM task types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 110 publications
2
121
2
Order By: Relevance
“…Further evidence for MPFC‐mediated self‐other equivalence comes from studies on self/other identification with a virtual avatar or trust during interactions with an artificial agent . Similarly, a wealth of evidence from human–human interaction supports the notion of a crucial role of the TPJ in inferring the mental states of others, in differentiating the self from others during joint attention and perspective taking tasks, as well when making judgments of in‐group versus out‐group members …”
Section: Integrative Perspectivementioning
confidence: 97%
See 1 more Smart Citation
“…Further evidence for MPFC‐mediated self‐other equivalence comes from studies on self/other identification with a virtual avatar or trust during interactions with an artificial agent . Similarly, a wealth of evidence from human–human interaction supports the notion of a crucial role of the TPJ in inferring the mental states of others, in differentiating the self from others during joint attention and perspective taking tasks, as well when making judgments of in‐group versus out‐group members …”
Section: Integrative Perspectivementioning
confidence: 97%
“…While these findings complement previously discussed findings of the role of the PPN, it is important to note that perception of social animations also engages brain activity beyond this network. For example, the goal‐directed movement of simple shapes triggers activation in the anterior intraparietal sulcus, part of the AON, similar to human goal‐directed movements, and social animations can be used to functionally localize the ToM network and robustly activate the TPJ …”
Section: Impact Of Artificial Agent's Visual Featuresmentioning
confidence: 99%
“…We study the association between functional lateralization and neurostimulation responsiveness by focusing on the temporoparietal junction (TPJ), which has received considerable interest in recent years as its nexus role in attention, memory, language, and social cognition . TPJ, especially the right TPJ, is a vital hub of the social brain .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of raw measures such as response time and accuracy with full factors was reported in the Supporting Information. Individual stimulation responsiveness was calculated for each participants using Equations(5)and(6).…”
mentioning
confidence: 99%
“…The TPJ is involved in multiple cognitive functions (Alkire, Levitas, Warnell, & Redcay, ; Baumgartner, Dahinden, Gianotti, & Knoch, ; Donaldson et al, ; Fujino, Yamasaki, et al, ; Mars et al, ; Soutschek et al, ). In particular, the right TPJ plays a key role in social cognition, such as perspective taking (Krall et al, ; Schurz, Tholen, Perner, Mars, & Sallet, ; Tei et al, ), moral decision‐making (Bitsch, Berger, Nagels, Falkenberg, & Straube, ; Chen, Decety, Huang, Chen, & Cheng, ; Tei et al, , ; Young, Camprodon, Hauser, Pascual‐Leone, & Saxe, ), and strategic social behavior (Hampton, Bossaerts, & O'Doherty, ; Hill et al, ). Significantly, previous fMRI studies have shown that the right TPJ plays a vital role in differentiating between in‐group and out‐group members in judgments and behavior (Baumgartner et al, ; Falk et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%